Crash or hug? A study on how pedestrians perceive safety of autonomous cars in parking garages - Karlsson, Douglas; Löfvenberg, Kristofer (My University, 2019)
Abstract The car industry is a line of business that constantly advances. The new technology has made it possible to let vehicles have driver support features to help the driver or overtake the steering. Automated Valet Parking (AVP) is an automated driving feature for autonomous vehicles, whose technique implements an automatic self-driving drive-up and park service in parking garages. The pedestrian-vehicle interaction har poorly been explored, especially in the context of a parking garage where the vehicle's speed is slow. For this reason, this master's thesis project has been to conduct a study about the interaction between pedestrians and self-driving vehicles in parking garages. The aim has been to investigate how autonomous vehicles' behaviour should be managed and perceived safety for pedestrians with the aim to deliver driving guidelines to autonomous vehicles in parking garages to maintain a perceived safety for pedestrians. The project developed several user tests in a parking garage, applied with a Wizard of Oz approach to illustrate a self-driving vehicle. The participants were acting pedestrians, and the experience of interacting with an automated vehicle was gathered with the emotional tool Self-Assessment Manikin and interviews. To evaluate the findings from the user tests, a validation test was performed, containing a sequence of similar situations as the user tests, but with another group of participants. The results showed that pedestrians have a perception of space they prefer to keep to a vehicle in slow speeds in order to perceived safety. That space has been identified as a comfort zone concerning both lateral and longitudinal distances to the vehicle. Additionally, the study found a body language of the car that increased the pedestrians understanding of what the car's behaviour intended to do. The findings got sum up to a final concept with guidelines to an autonomous vehicle with the autonomous feature Automated Valet Parking. Keywords: Autonomous vehicle, automated valet parking, pedestrian, interaction, emotional experience, perceived safety, body languish, comfort zone, autonomous vehicles.
Keywords: Autonomous vehicle, automated valet parking, pedestrian, interaction, emotional experience; perceived safety, body languish, comfort zone, autonomous vehicles